Metaforiskie hidronīmi Latvijā - Balode, Laimute (Baltistica, 2012)
METAPHORIC HYDRONYMS IN LATVIASummaryA metaphor – a term or phrase applied to something which it is not literally applicable to – usually constructs an analogy between two things. This creates associative perception. There are quite a few Latvian toponyms as well as hydronyms made on the basis of indirect comparison: Latv. lake-names Āķis ʻcrook, hookʼ, Panna ʻfrying-panʼ, Baļļa ʻtubʼ may stress the configuration of the hydroobject, Latv. river-name Adatiņa ʻneedleʼ describes the stream of the brook. There are many more compound hydronyms and multi-word names which could be perceived as metaphorical: Latv. lake-names Garasts ʻlong taleʼ, Velna acs ʻDevilʼs eyeʼ, etc.Metonymical hydronyms are names of objects in one or another way associated with hydroobjects, e.g. Latv. lake-name Zuosins ‘gander’, Dunkurs ‘net’. Another possible way of coining hydronyms is synecdoche, i.e. using the name of a part of some object as the name of the whole object, for example, Pakavlīcis ʻhorseshoe bay’ – the bay name which is used as the name of the lake. Metaphor, metonymy and perhaps synecdoche in toponymy, particularly in hydronymy, are still an unexplored field of Baltic onomastics.